Multi-criteria discovery, design and manufacturing to realise nanomaterial potential - Robert Pilling; Stuart R. Coles; Marc R. Knecht; Siddharth V. Patwardhan (Communications Engineering, 2023)
Nanomaterial solutions to sustainable development goals are hindered in their path to commercialisation by an early-stage reliance on single metric optimisation. Here we formulate the PSEC challenge (Performance, Scalability, Environment and Cost) to integrate broader sustainability thinking with precise technical solutions and so enable successful commercialisation of these advanced materials.